EXECUTIVE’S REWARDS AND THEIR CHANGES IN THE LITHUANIAN PUBLIC SECTOR - Kazakevičius, Giedrius (Politologija, 2015)
The article deals with contemporary executive’s rewards system in the Lithuanian public sector and its changes over time. This analysis includes high officials in civil service as well as heads of public service’s providers and managers of state-owned enterprises. The analysis bases on the reward dimension of the Public Service Bargains (PSBs) model which reflects different approaches to tangible and intangible reward elements. This theoretical approach is used to test the hypotheses that there is a clear public sector bargain on the executive’s rewards system, and this bargain was shaped by pre-planned reforms in the public sector. The analysis of the legal framework of the tangible reward system explains how egalitarian bargain was consolidated in the fragmented public service system, and pre-planned reforms added some hierarchical and individualistic elements to this system. The assessment of the Lithuanian public sector executives’ tangible rewards in the international context, differentiation among different types of Lithuanian public sector organizations and inside organisations itself provides clear evidences that the egalitarian reward type dominates in the Lithuanian public service. The refusal by politicians to align the reward system periodically with changes in economic conditions during growth times also strengthens this egalitarian element. Recent public deliberations allow to assess how divergent are approaches by politicians and high public officials to the contemporary executive’s reward system. On the one side, there is a broad political coalition which in a consistent way supports the egalitarian approach to the executive’s reward system. On the other side, high civil service officials follow the logic of the hierarchical system and use judicial measures to protect their interests. An overview of the intangible reward elements in the Lithuanian public sector also shows supporting evidence to the egalitarian reward system. In this context, notable is the failure to introduce a clear career path as the key element of the hierarchical system. This article concludes that the Lithuanian public sector executive reward system can be regarded as egalitarian and was largely shaped by incremental policy decisions, changes in economic conditions, and court decisions but not by pre-planned reforms.